The Influence of Self Instructional Module (SIM) Airway Management on Nursing Students' Knowledge (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction : Clinical practice is an important part of the nursing education process.  The need for learning strategies can facilitate student learning to create a conducive learning environment. One learning method that can be used is Self Instruction Metode (SIM) because students can study independently without depending on other people. It is hoped that students in the teaching and learning process can be more active and easier in acquiring knowledge, especially emergency knowledge. Emergency problems that often occur both in the pre-hospital and intrahospital stages are airway problems or airway. Sufficient knowledge will influence student performance later in facing real emergency environments, especially in practice areas. Objective: find out the effect of SIM as a learning method on knowledge about airway management in nursing students. Method: Pre-experimental research using one group pretest posttest design. Samples were selected randomly  probability sampling with method consecutive sampling a total of 38 IKesT Muhammadiyah Palembang students. The research instrument uses modules airway management and knowledge questionnaire. Results : Based on data analysis with tests Wilcoxon obtained p value